TALKING CHIPS TECHNIQUE TO TEACH SPEAKING - Muhammad Muklas (Pendidikan Bahasa Inggris STKIP Nurul Huda, 2017)
This research aims to find the Effectiveness of Talking Chips Technique to Teach Speaking at the Eleventh Grade Students of SMK. The problem of the research is formulated “Is there any significant differences between students who are taught by using Talking Chips Technique and students who are taught by using Conventional Technique in teaching speaking to the eleventh grade students of SMK. Moreover, the objective of this study was to know whether or not there is significant difference between students who are taught by using Talking Chips Technique and the students who are taught by using Conventional Technique in teaching speaking to the eleventh grade students of SMK . This research was quantitative research, using experimental method and true experimental design. Then, the population of the study covered the entire of eleventh grade students of SMK in academic year 2016/2017 with total students were 318 from ten classes. And the sample of the study were 62 students, consist of two groups, namely experimental group (XI.9) consist of 31 students and control group (XI.10) consist of 31 students which is choosen by cluster random sampling. In this study, the writer used speaking test as an instrument for collecting the data. The data obtained from Independent t-test analysis, between the result of posttest in experimental group and control group. Based on the calculation by using Independent t-test, the writer found that t obtained was higher than t table (2,62 > 2,000) at the significant level α = 0.05 in two tailed testing. It means that there was any significant differences between experimental group and control group. So, the null hypothesis (Ho) was rejected and alternative hypothesis (Ha) was accepted. It can be concluded that Talking Chips Technique was significantly effective in teaching speaking to the eleventh grade students of SMK.